Estimating Population Density of Himalayan Rangeland Weed Senecio chrysamthemoides DC. - Limbu, Dil Kumar; Khatiwada, Ram Prasad; Koirala, Madan (Our Nature, 2013)
Unpalatable and unwanted native or invasive plants that have adverse impact on the forage in the grazing area are rangeland weed. Climate change, introduction of new species, disturbance and fragmentation of land are causative factors for spreading native or invasive weed infestation on rangelands. Senecio chrysanthemoides is a serious obnoxious weed on Himalayan rangeland area. It is densely populated on plain and left places of shed constructed area consequent rangeland degraded, displacing desirable species, degrading systems, decreasing productivity and increase management costs. To arrest infestation of weed, mechanical control measure was followed but unplanned mechanical control measure was inadequate. Up-rooting weed earlier flowering was more effective than other life form of weed. DOI: http://dx.doi.org/10.3126/on.v10i1.7745